Faktor yang Mempengaruhi Kualitas IPK Mahasiswa di Jurusan Matematika FMIPA UNP Menggunakan Regresi Logistik - Prida Nova Sari; Yenni Kurniawati; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – Grade Point Academic (GPA) is a standard of university student academic achievement. In job competition, college graduates required to be more creative to develope their potential. GPA is one form of self-potential required by companies headhunter. The achievement of a high GPA is expected to facilitate the college graduates to get a job. The factors that affect GPA is why choose math major, college entrance, father’s occupation, mother’s occupation status, maintenance, residence condition, travel time to campus, length of study, completeness reference books, active organizationsi, and history of serious illness. If the dominant factor known, then GPA can be maximized. Therefore, formulation of the problem in research is how the logistic regression model to identify factors that affect the quality of GPA student majoring in Mathematics in State University of Padang. Factors affecting the quality of GPA student majoring in Mathematics in State University of Padangare father’s occupation, completeness reference books and history of serious illness.Keywords – GPA, Self-Potential, Logistic Regression Analysis.